10 Recommended core outcome domains for tendinopathy derived from a delphi of patients and health care professionals: the groningen ISTS2018 consensus. (April 2019) - Vicenzino, Bill; Vos, Robert-Jan de; Alfredson, Håkan; Bahr, Roald; Carr, Andrew; Cook, Jill; Coombes, Brooke; Ngor Fu, Siu; Gravare Silbernagel, Karin; Grimaldi, Alison; Lewis, Jeremy; Maffulli, Nicola; et al.
Abstract : Introduction: Tendinopathy (local tendon pain associated with physical activity) is a challenge to treat despite recent advances. One factor contributing to this challenge is our limited ability to synthesise/meta-analyse research findings, which is further compounded by a lack of valid outcome measures. We determined the core outcome domains against which outcome measures could be recommended. Materials and methods: We conducted a Delphi study of patients and health care professionals (HCP) in two parts: an online survey and consensus meeting. Online survey items were extracted from clinical trial reports. Agree, disagree, or unsure were options in response to: 'The 'item' is important enough to be included in a core domain set of tendinopathy'. A-priori criterion of ≥70% participant agreement was deemed for selection of a core domain. Results: 32 patients and 28 HCP (92% had >10 years of tendinopathy experience, 71% consulted >10 cases per month) completed the online survey. 2 patients and 15 HCP attended the consensus meeting. Of the original 24 items (from trial reports); 9 were core: Patient overall rating, participation, pain on activity/loading, disability, function, physical function capacity, quality of life, psychology, and pain over a specified timeframe. Eight items were not core domains: range of motion, palpation, clinical examination, structure, pain on examination or without other specification, drop out, and sensory modality pain. Remaining seven items did not meet criterion. Conclusion: The core domain set serves as a guide for reporting of outcomes in clinical trials. Further research should determine these outcomes for each specific tendon.